2012
DOI: 10.1021/jp3119617
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Autoionization of Water at Phospholipid Interfaces

Abstract: ABSTRACT:The structure and autoionization of water at the water−phospholipid interface are investigated by ab initio molecular dynamics and ab initio Monte Carlo simulations using local density approximation (LDA) and generalized gradient approximation (GGA) for the exchange−correlation energy functional. Depending on the lipid headgroup, strongly enhanced ionization is observed, leading to the dissociation of several water molecules into H + and OH − per lipid. The results can shed light on the phenomena of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
(65 reference statements)
1
15
0
Order By: Relevance
“…The approach could also be combined with more accurate simulation of bilayers. Full atomistic simulations and in particular ab initio simulations, could in principle provide more accurate descriptions of the system but comes with a huge computational burden (Mashaghi et al, 2012 , 2013a ).…”
Section: Resultsmentioning
confidence: 99%
“…The approach could also be combined with more accurate simulation of bilayers. Full atomistic simulations and in particular ab initio simulations, could in principle provide more accurate descriptions of the system but comes with a huge computational burden (Mashaghi et al, 2012 , 2013a ).…”
Section: Resultsmentioning
confidence: 99%
“…Self assembly of phospholipids results in bilayers or monolayers. Bilayers are birefringent [28], thermally conductive (energy transfer on sub-picosecond time scales; κ~several Watt/mK [20]), behave as insulators perpendicular to the membrane and in the core part whereas they are electrically conductive within the plane of the membrane due to proton hopping in the interfacial water [29]. Assembled bilayers display different phases depending on the temperature ( T ) and pressure ( P ) of the environment.…”
Section: Figurementioning
confidence: 99%
“…At these concentrations, the bulk-phase pH would be equivalent to approximately 1.4 and 0.4, respectively, and thus significantly lower than the pH values used for experiments reported in Cranfield et al, which were carried out at pH 5 (Cranfield et al 2016). However, a number of experimental and computational studies have suggested that the local concentration of H 3 O + ions at the water-lipid interface is significantly higher than that in the bulk water phase (Brändén et al 2006;Gopta et al 1999;Heberle et al 1994;Slevin and Unwin 2000;Mashaghi et al 2013;Smondyrev and Voth 2002;Wolf et al 2014;Yamashita and Voth 2010) resulting in differences of up to four pH units.…”
Section: Introductionmentioning
confidence: 99%